Qualidade de cebola minimamente processada em diferentes tipos de cortes - Antunes, Andréa Maria [UNESP] (2014)
The high perishability of the onion has limited its conservation period and caused great post-harvest losses. The need of consuming fresh products has led the market of minimally processed products to considerably rise. Cut operations during the minimal processing may not only cause important biochemical reactions in the onion tissues, but also affect its sensorial quality, resulting in a drastic reduction in the post-harvest life of the product. In this study the influence of different cut types was assessed on the quality of minimally processed onions. 'Baia Periforme'onions were transported to the laboratory, where they were selected, cleaned, classified, peeled, minimally processed into slices, grated and chopped, and subsequently sanitized for 10 minutes in sodium hypochlorite at 100 mg L-1. The product was kept on polystyrene trays covered with plastic film (PVC) as 80 g portions and conserved in a cold chamber at 5 +/- 1 degrees C and 85 +/- 5% RH, during 6 days. Physical, chemical and physico-chemical assays were carried out. Statistical design was completely randomized with 3 treatments and 3 replications (plot group) and 5 replicationss for the control group. For sensorial analysis (aspect and smell), 10 replications were used. To compare means, Tukey test at 5% significance was adopted. During the refrigerated conservation, sliced onions kept more stable levels of soluble solids, titratable acidity, total sugars, reducing and non-reducing sugars. The grated onion was superior considering the sensorial characteristics, indicating that the cut types interfered in these features and the grated onion was more accepted by evaluators.